2003
DOI: 10.2166/wst.2003.0251
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of solventogenic, cellulase-free xylanolytic Clostridia from cow rumen

Abstract: Hemicellulolytic obligate anaerobes capable of converting a range of agricultural substrates and monomeric sugars of hemicellulose to solvents and acids were isolated from cow rumen fluid. The strains were identified as 5 strains of C. beijerinckii (3 different genotypes), 3 strains of C. acetobutylicum (2 different genotypes), 1 strain of C. butyricum and 3 strains of C. bifermentans (2 different genotypes). All of them produced cellulase-free xylanase activity. C. acetobutylicum LU1 produced solvent, a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Nevertheless, we also found a substantial number of ESTs with a bacterial Best Hit. The Bacterium with the most Best Hits is Clostridiumacetobutylicum , a Firmicute which has previously been isolated from bovine rumen fluid [ 17 ]. A total of 11 different Firmicutes were identified with Best Hits, plus nine "other" Bacteria and two Archaea species.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we also found a substantial number of ESTs with a bacterial Best Hit. The Bacterium with the most Best Hits is Clostridiumacetobutylicum , a Firmicute which has previously been isolated from bovine rumen fluid [ 17 ]. A total of 11 different Firmicutes were identified with Best Hits, plus nine "other" Bacteria and two Archaea species.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, some solventogenic Clostridium strains, such as C. beijerinckii NCIMB 8052 and IBUN 125C, and C. acetobutylicum IBUN 13A and 18A, expressed multiple saccharolytic enzymes including cellulase, xylanase and amylase [14]. Similarly, a few other Clostridium strains such as C. beijerinckii LU-1 and Clostridium bifermentans LU-1 were reported to express xylanase [15]. Recently, we also reported that a Clostridium strain BOH3 expressed both xylanase and amylase during fermentation [16,17].…”
Section: Introductionmentioning
confidence: 86%
“…Lignocellulose is significantly more recalcitrant to biodegradation than traditional ABE fermentation feedstocks. The four main native butanol producers, C. acetobutylicum , Clostridium beijerinckii , Clostridium saccharobutylicum , and Clostridium saccharoperbutylacetonicum (Gu et al, 2011 , 2014 ), cannot directly grow on lignocellulose (Lee et al, 1985 ; Levi Hevroni et al, 2020 ; Sabathé et al, 2002 ; Sankar et al, 2003 ). Therefore, inefficient multistep processes are required for fermenting lignocellulose to butanol which features biomass pre‐treatment and/or dedicated cellulase production and/or separated biomass saccharification and/or hexose and/or pentose fermentation (Figure 1 ) (Mazzoli, 2020 ; Tarraran & Mazzoli, 2018 ).…”
Section: Introductionmentioning
confidence: 99%